International educational governance - Amos, S. Karin (International perspectives on education and society, 2010)
This volume pursues two central objectives. On the one hand, it is necessary to sharpen our analytical tools in order to better appreciate the term governance in the educational field. To this end the five different paradigmatic approaches on governance as well as different topics and sectors shall be confronted/contrasted and related to each other. In the course of this process, the particularly critical educational issue of the relation between academic analyses of governance and the so called governmentality studies will be discussed. On the other hand, the so far marginally studied issue of change in the 'educational science order' will be addressed. The transformations mentioned affect the nucleus of the pedagogical understanding of education. The promise of a greater adequacy to the needs and interests of those addressed by education, because more flexible, more user-oriented, more precise control of effects presents a challenge to educational science and pedagogy. This marks the interface of "governance" and "performance" on a systems or organization level (Soguel/Jaccard, 2008; Simons, 2007) with the individual as the subject of education.